MU-math: educational game to improve students’ mathematical reasoning - M Daenasty Caezar Zahra; Susi Setiawani; Saddam Hussen (Jurnal Riset Pendidikan Matematika, 2022)
Learning media are tools utilized to support the interaction of students with educators and learning resources in the implementation of the teaching and learning process. This development research uses the Thiagarajan or 4-D model with four stages: defining, designing, developing, and disseminating. The subjects of this research were grade VIII students of SMP Negeri 1 Umbulsari. The analytical method is validity analysis based upon validation by two lecturers of the Mathematics Education Study Program, FKIP University of Jember, and one mathematics teacher from SMP Negeri 1 Umbulsari.  Practicality analysis was based on user response questionnaires and interviews, and effectiveness analysis using pretest/pretest and final test/posttest. This study uses the educational Game Mu Math on numbering pattern material to improve students' mathematical reasoning with the help of Unity software. MU Math Game is a PC (Personal Computer) based Game developed using Unity Engine Software and Lego Assets Tools. The MU Math game is an Adventure Open world type where players can explore through the maps provided. There are two levels and one mathematical reasoning to test students' mathematical reasoning abilities.